2021
DOI: 10.1155/2021/4106882
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Portfolio Assessment on Iranian EFL Learners’ Autonomy and Writing Skills

Abstract: The portfolio assessment is a purposeful and systematic collection of students’ work that is intended to show progress over time. The researchers employed the Oxford quick placement test, autonomy questionnaire, and topic-based paragraph writings as the pretest and posttest. The design of the study was quasiexperimental. To this end, researchers chose 120 learners with the convenience sampling method, which were 60 learners at the upper-intermediate and 60 learners at the advanced level. Participants were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
0
0
Order By: Relevance
“…Their study revealed that using authentic assessment as a sort of presentation task could improve learners' reading skills by providing evidence of reactions to students' written literary works. Furthermore, the findings of Biglari et al (2021) showed that the portfolio assessment, a type of authentic assessment, produced a construction impact on Iranian EFL students' autonomy at both upper-intermediate and advanced levels is consistent with the findings of the current study. They also revealed that portfolio assessments generated a constructive important impact on the writing skills of Iranian EFL students.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Their study revealed that using authentic assessment as a sort of presentation task could improve learners' reading skills by providing evidence of reactions to students' written literary works. Furthermore, the findings of Biglari et al (2021) showed that the portfolio assessment, a type of authentic assessment, produced a construction impact on Iranian EFL students' autonomy at both upper-intermediate and advanced levels is consistent with the findings of the current study. They also revealed that portfolio assessments generated a constructive important impact on the writing skills of Iranian EFL students.…”
Section: Discussionsupporting
confidence: 90%
“…The portfolio assessment is a purposeful and systematic collection of student's work that is intended to show progress over time. Portfolio assessment has been used as an alternative approach to standardized testing for more than two decades (Biglari et al, 2021). It commonly refers to a print or web-based dossier, where students regularly revisit and evaluate their learning trajectories by way of multimodal artifacts (Muin et al, 2021).…”
Section: Portfoliosmentioning
confidence: 99%
“…Finally, the results of the study advocated the findings of Pourdana and Tavassoli [31]. In addition, the results of the study lend credence to the findings of Biglari et al [35]. ey found that the portfolio assessment significantly improved Iranian EFL learners' writing skills and autonomy.…”
Section: Discussionsupporting
confidence: 78%
“…As an ongoing process, portfolio development exhibits a learner's problem-solving, decision-making and critical thinking skills (Baturay and Daloglu (2010), and enhance their learning within social contexts (Bagheri & Ghaffari, 2017). Furthermore, developing a portfolio enables students to enhance their writing skill (Efendi, 2017;Biglari, Izadpanah & Namaziandost, 2021), encourage them to represent and integrate their formal and informal learning experiences (Chen and Light, 2010) and enhance their active learning in different ways (Pospisilova, 2018). A digital or an electronic portfolio provides more advantages than the regular portfolios (Hung, 2008in Baturay & Daloglu, 2010.…”
Section: Portfolio Developmentmentioning
confidence: 99%